Comparing Several Treatments with Antibiotics for Community-Acquired Pneumonia: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Fusheng Bai; Xinming Li (Tehran University of Medical Sciences, 2021)
Background: We aimed to review relevant randomized controlled trials to assess the relative clinical effects of antibiotic treatment of patients with community-acquired pneumonia (CAP). Methods: In this meta-analysis, we identified relevant studies from PubMed, Cochrane, and Embase using appropriate keywords. Key pertinent sources in the literature were also reviewed and all articles published through Oct 2019 were considered for inclusion. For each study, we assessed the risk ratios (RRs) or mean difference combined with the 95% confidence interval (CI) to assess and synthesize outcomes. Results: Overall, 36 studies were consistent with the meta-analysis, involving 17,076 patients. There was no significant difference in the mortality after subgroup analysis: individualized treatment vs. standard treatment; β-lactams plus macrolides vs. β-lactam and/or fluoroquinolone; ceftaroline fosamil vs. ceftriaxone; combination therapy vs. monotherapy or high-dose vs. low-dose. The drug-related adverse event incidence was significantly higher in the ceftriaxone group than in the other drug groups (P<0.05) and also higher in the tigecyline group than in the levofloxacin group (P<0.05). Compared with ceftriaxone, ceftaroline fosamil significantly increased the clinical cure rate at the test-of-cure (TOC) visit in the clinically evaluable population, modified intent-to-treat efficacy (MITTE) population, microbiologically evaluable (ME) population and the microbiological MITTE (mMITTE) population (all P<0.05). Compared with ceftriaxone, ceftaroline fosamil significantly increased the clinical cure rate at the TOC visit in the mMITTE population of Gram positive-Streptococcus pneumoniae (P<0.05) and multidrug-resistant S. pneumoniae (P<0.05). Conclusion: There was a limited number of included studies in the subgroup analysis, but it will still be necessary to conduct more high-quality randomized controlled trials to confirm the clinical efficacy of different antibiotics used to treat CAP.